Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1972
DOI: 10.1002/chin.197246183
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: UNTERSUCHUNGEN AN CHALKONEN, VERHALTEN GEGENUEBER GRIGNARDREAGENTIEN UND BEI FRIEDEL‐CRAFTS‐RK.

Abstract: "In Aus den Chalkonen (I) erhält man bei der Reaktion mit Grignardverbindungen (II) die Propiophenone (III); einzelne Vertreter werden z.B. durch Friedel‐Crafts‐Reaktion der Säurechloride (IV) mit den Aromaten (V) hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also they showed significant cytotoxicity against both human prostate and breast cancer cell lines 12 . The previous studies indicated the importance of 3',4'-disubstitution on the phenyl rings for the activity of α,β-unsaturated ketones in the synthesis of variety of organic products having different applications [13][14][15][16] . Recently, we studied the reaction of (…”
Section: Introductionmentioning
confidence: 99%
“…Also they showed significant cytotoxicity against both human prostate and breast cancer cell lines 12 . The previous studies indicated the importance of 3',4'-disubstitution on the phenyl rings for the activity of α,β-unsaturated ketones in the synthesis of variety of organic products having different applications [13][14][15][16] . Recently, we studied the reaction of (…”
Section: Introductionmentioning
confidence: 99%
“…Thiourea reacts with ,/3-unsaturated ketones to give 2-thiopyrimidine derivatives (9, 10, 12, [15][16][17]. Thus, when 4-arylmethylene-3,4-dihydro-1-benzothiepin-5(2H)one 1,1-dioxides (I) were fused with thiourea at about 200°, they formed 1-benzothiepino [5,4-d]pyrimidine-10thione 5,5-dioxides (II).…”
mentioning
confidence: 99%